The European economic crisis from 2007 onwards in the context of a global crisis of over-production of capital - a Marxian monetary theory of value interpretation - Sascha Gander (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
This paper attempts to clarify how the European economic crisis from 2007 onwards can be understood from the perspective of a Marxian monetary theory of value that emphasizes in-trinsic, structural flaws regarding capitalist reproduction. Chapter two provides an empirical description of the European economic crisis, which to some extent already reflects the struc-tural theoretical framework presented in chapter three. Regarding the theoretical framework Michael Heinrich's interpretation of 'the' Marxian monetary theory of value will be presented. Heinrich identifies connections between production and realization, between profit and inter-est rate as well as between industrial and fictitious capital, which represent contradictory tendencies for which capitalism does not have simple balancing processes. In the context of a discussion of 'structural logical aspects' of Marx's Critique of the Political Economy, explana-tory deficits of Heinrich's approach are analyzed. In the following, it is argued that Fred Mose-ley's view of these 'structural logical aspects' allows empirical 'applications' of Marxian mon-etary theories of value. It is concluded that a Marxian monetary theory of value, with the characteristics of expansive capital accumulation and its limitations, facilitates a structural analysis of the European economic crisis from 2007 onwards. In this line of argument, expan-sive production patterns are expressed, among other things, in global restructuring processes, while consumption limitations are mitigated by expansive financial markets and shifts in ex-port destinations.
Keywords: B51; B59; D30; D46; E11; E21; E22; E23; E40; E50; F10; F21; F60; G15; G18; G20; N10; N20; O52; P16; 330; Marxian monetary theory of value; change in plan debate; ideal average; transfor-mation problem; European economic crisis; overproduction; Heinrich; Moseley